PENERAPAN MODEL PEMOLISIAN BERBASIS MASYARAKAT (COMMUNITY POLICING MODEL) DI KEPOLISIAN RESOR MOJOKERTO - Praptama, Khansa Fernanda Fa'iq; Hartoyo, Hartoyo; Damayanti, Sri Sukmana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze how the community policing model is implemented in the Mojokerto Police and identify the challenges faced in its implementation, particularly in relation to the quality of human resources. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the implementation of Community Policing at the Mojokerto Police Station has been carried out through the active role of Bhabinkamtibmas, outreach activities, legal counseling, and the formation of FKPM. This implementation has increased community involvement in maintaining security and public order. However, the quality of human resources remains a significant obstacle, especially in terms of social competence, workload, and the availability of community-based training. The success of Community Policing is highly dependent on the interpersonal capacity of officers and the level of community participation. Intensive training, work system reform, and the strengthening of social partnerships are needed so that this model can be implemented optimally and sustainably